2008
DOI: 10.1007/s00259-007-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal crises following receptor radionuclide therapy with the radiolabeled somatostatin analogue [177Lu-DOTA0,Tyr3]octreotate

Abstract: IntroductionReceptor radionuclide therapy is a promising treatment modality for patients with neuroendocrine tumors for whom alternative treatments are limited. The aim of this study was to investigate the incidence of hormonal crises after therapy with the radiolabeled somatostatin analogue [177Lu-DOTA0,Tyr3]octreotate (177Lu-octreotate).Materials and methodsAll 177Lu-octreotate treatments between January 2000 and January 2007 were investigated. Four hundred seventy-six patients with gastroenteropancreatic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 22 publications
0
67
0
1
Order By: Relevance
“…Prolonged or (re-)hospitalisation after therapy because of probably PRRT-induced hormonal crises occurred in six (1%) patients (de Keizer et al 2008). All patients recovered after adequate care including fluid infusion, high-dose i.v.…”
Section: Lu-labelled Somatostatin Analoguesmentioning
confidence: 99%
“…Prolonged or (re-)hospitalisation after therapy because of probably PRRT-induced hormonal crises occurred in six (1%) patients (de Keizer et al 2008). All patients recovered after adequate care including fluid infusion, high-dose i.v.…”
Section: Lu-labelled Somatostatin Analoguesmentioning
confidence: 99%
“…Safford et al also reported two deaths from myocardial infarction following high dose 131 I-MIBG therapy with a dose of 300 mCi (11.1 GBq) [22]. However, a 177 Lu-DOTATATE treatment-induced catecholamine crisis in a pheochromocytoma or paraganglioma patient has been described in only one case of malignant pheochromocytoma, in which the patient developed hypotension, excessive sweating and cardiac ischemia 1 day after 177 Lu-DOTATATE therapy [23]. The patient was pre-treated with corticosteroids for subsequent treatments; however, the authors did not provide further details.…”
mentioning
confidence: 99%
“…(Ahlman et al, 1987;Marsh et al, 1987;Roy et al, 1987;Ahlman et al, 1988a;Ockert and White, 1988;Darby et al, 1990;Debas and Mulvihill, 1994;Deguchi et al, 1994;Parry et al, 1996;Pekarek et al, 1997;Balestrero et al, 2000;Janssen et al, 2000;Kharrat and Taubin, 2003;Zimmer et al, 2003;Koopmans et al, 2005;Davi et al, 2006;Majeed et al, 2007;Papadogias et al, 2007;De Keizer et al, 2008;McPherson et al, 2009;Sinha et al, 2009;Yazbek-Karam et al, 2009;Fujie et al, 2010;Morrisroe et al, 2012;Raikhelkar et al, 2012;Shah et al, 2012;Massimino et al, 2013;van Diepen et al, 2013) The prophylactic usage of SSTA was diverse between different studies varying from long acting SSTA to continuous somatostatin infusion. Of the 28 patients with known demographic information, 17 cases (60.7%) were men and 11 cases (39.3%) were women.…”
Section: Resultsmentioning
confidence: 99%